Clinical practice in the management of postoperative delirium by Chinese anesthesiologists: a cross-sectional survey designed by the European Society of Anaesthesiology. Issue 6 (June 2020) - Delp, Simon; Mei, Wei; Spies, Claudia D.; Neuner, Bruno; Aldecoa, César; Bettelli, Gabriella; Bilotta, Federico; Sanders, Robert D.; Kramer, Sylvia; Weiss, Bjoern
Objective: In this survey, we assessed the current clinical management of postoperative delirium (POD) among Chinese anesthesiologists, after publishing the European POD guideline. Methods: We administered an electronic survey, designed according to the European POD guideline. The survey was completed using mobile devices. Results: In total, 1, 514 respondents from China participated in the survey. Overall, 74.4% of participants reported that delirium is very important. More than 95% of participants stated that they routinely assessed POD. In total, 61.4% screened for POD using clinical observation and 37.6% used a delirium screening tool. Although the depth of anesthesia (a POD risk factor) was monitored, electroencephalogram monitoring was unavailable to 30.6% of respondents. Regarding treatment, only 24.1% of respondents used a standard algorithm; 58.5% used individualized treatment. Conclusion: Our survey showed that there are high awareness levels among Chinese anesthesiologists regarding the importance of POD. However, routine assessment and monitoring of all patients, including perioperative anesthesia depth monitoring, and a treatment algorithm need to be implemented on a larger scale. According to the results, efforts should be made to improve the knowledge of POD among Chinese anesthesiologists.